Edukacja w zakresie praw człowieka - Koba, Laura (OTO Agencja Reklamowa, 2014)
Education is currently one of the key social issues in the focus of interest of many international organisations and particular states alike. The main reason is the process of transformation of industrial society into a global information society, which has been in progress for many years. Education was supposed to make people aware of serious problems of today's world. It was then when slogans of „learning without borders” and „lifelong learning” started to be introduced by international organisations. Thanks to U.S. President Jimmy Carter, also human rights appeared in the centre of attention of the education sector as President Carter made them a part of “the reality of international politics. Relying on UNESCO guidelines, education should reflect ideas „based upon the hope for a world that is a better place to live in, where people will have learned to respect the rights of women and men, to show mutual understanding, and to use advances in knowledge to foster human development rather than to create further distinctions between people”. For practical purposes, human rights education has been defined by almost all international organisations. Working out a common definition of human rights education – a notion used in wider context that included also civic education, and education for respect and understanding – by various international organisations, namely UNESCO, UN High Commissioner for Human Rights, Office of Democratic Institutions and Human Rights, and the Council of Europe and others proved to be a success. Thus, human rights education is understood both as teaching activities, training courses and as providing various information that are aimed at building a common culture of human rights. Comprehensive human rights education provides not only knowledge on them and mechanisms of their protection but also skills necessary to exercise them in everyday life.
Keywords: organizacje międzynarodowe; politologia; prawa człowieka; demokracja; pomoc humanitarna; migracje; patologie; bezpieczeństwo; terroryzm międzynarodowy; ochrona środowiska